IMPROVING STUDENTS™ SPEAKING ACHIEVEMENT IN AGREEMENT AND DISAGREEMENT EXPRESSIONS BY USING PROBLEM SOLVING STRATEGY AT GRADE VIII SMP SWASTA HKBP SIDORAME MEDAN - Sitohang, Angelina -; Siregar, Masitowarni - (Universitas Negeri Medan, 2014)
ABSTRACT This study deals with the improving students™ speaking achievement in agreement and disagreement expressions by using problem solving strategy. The objective of this study is to find out whether students™ speaking achievement in expressing agreement and disagreement improved by problem solving strategy. The effectiveness of problem solving strategy are to make the students able to help them in solving their own and friends™ problems, especially classmates™ problem by expressing agree or disagree to the solution made and students be more active in the classroom. The findings of this study are important and useful for English teachers to improve students™ interest and ability in speaking by problem solving strategy and the researcher who wants to conduct the research related to this study. This study was conducted by using classroom action research. The subject of this research was the second grade of SMP Swasta HKBP Sidorame Medan which consisted of 38 students. The research was conducted in two cycles, namely cycle I and cycle II. Each cycle consisted of the four steps of an action research: planning, action, observation and reflection. The instruments for collecting data used speaking test by interview and for the quantitative data and used diary notes, observation sheet and interview sheet for qualitative data. Based on the speaking test result, the students score kept improving in every test. In the orientation test the mean of the students™ score was 22.3. In the post test cycle I the mean of the students™ score was 56.3 and in the post test cycle II the mean of the students™ score was 85. Based on the observation sheet, diary notes and interview sheet, it was found that teaching learning process ran well. The conclusion is that Problem Solving Strategy improves students™ speaking achievement. Keywords : Speaking, Agreeing and Disagreeing Achievement, Agreement and Disagreement Expressions, Problem Solving Strategy